Faktor-Faktor Penyebab Masalah Pokok Pembangunan Ekonomi di Era Globalisasi di Indonesia - Mira Yuli; Septia Arum Ningsih; Gama Pratama (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
This study analyzes the factors causing the main problems in economic development during the era of globalization, as well as the resulting impacts, both positive and negative. The approach used is qualitative, based on a literature review of academic publications and relevant sources. The findings indicate that economic development is primarily characterized by an increase in per capita income and community prosperity. However, it also faces several challenges, including poverty, unemployment, inflation, and low human development, all exacerbated by advances in information technology, transportation, international trade, and the ideology of free markets. While globalization offers significant opportunities for economic growth, it also brings challenges that require careful management. The positive impacts include increased access to global markets and technological advancements, while the negative impacts involve widening inequality and cultural erosion. This study offers recommendations for addressing these issues, such as strengthening government regulations, improving organizational strategies, preserving local culture, and focusing on human resource development. It is hoped that this study will serve as a reference for formulating inclusive and sustainable economic development policies in the globalized era.